2021
DOI: 10.35229/jaes.958049
|View full text |Cite
|
Sign up to set email alerts
|

Tuz Stresinin (Potasyum Klorür) Aspir (Carthamus tinctorius L.) Çeşitlerinin Ekolojik ve Fizyolojik Özelliklerine Etkisi

Abstract: Salinity, which is a significant abiotic stress factor, is among the most important factors that limit product quality and yield. In this study investigated phenological and physiological changes that occurred in three different safflower varieties that were exposed to KCl stress at concentrations of 0, 50, 100 and 150 mM. It was found that, based on increasing salt concentrations, the most significant decrease was in all phenological parameters at the concentrations of 100 and 150 mM KCl. The SOD and CAT acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previously, it was reported that treatment with 300 mM KCl in Chenopodium album reduced growth and significantly reduced carotenoid levels ( Yao et al., 2010 ). With rising concentrations of 50, 100, and 150 mM of KCl salt, the root and shoot growth of Carthamus tinctorius L. was also reduced ( Leblebİcİ et al., 2021 ). The growth of Triticum aestivum L. was reduced by more than 60 ppm of KCl ( Rasheed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that treatment with 300 mM KCl in Chenopodium album reduced growth and significantly reduced carotenoid levels ( Yao et al., 2010 ). With rising concentrations of 50, 100, and 150 mM of KCl salt, the root and shoot growth of Carthamus tinctorius L. was also reduced ( Leblebİcİ et al., 2021 ). The growth of Triticum aestivum L. was reduced by more than 60 ppm of KCl ( Rasheed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%